New triterpenoids and sterol with potent cytotoxic activity from Justicia simplex - Isolation, characterisation and biological evaluation - Litty Joseph; K.K. Srinivasan (Elsevier, 2022)
Justicia is the largest genus of Acanthaceae family with nearly 600 species. Approximately eighteen species were chemically and biologically studied. Attempts were made to isolate, characterize and study the cytotoxic properties of three-petrol ether soluble components namely Methyl-(3β)-3, 23 dihydroxy olean-12-en-28-oate, 3β (Valeryloxy) olean-5,12-dien-1β, 11α, 28β -triol and Stigmasta-5, 20-dien-3β -yl undecanoates were isolated for the first time from this plant. The in vitro antiproliferative potential was assessed against MCF-7 and HeLa cells using MTT assay. 3β (Valeryloxy) olean-5,12-dien-1β, 11α, 28β -triol exhibited cytotoxicity in vitro with an IC50 value of 20.55 and 22.14 µg/mL for HeLa and MCF-7 cell lines respectively, which may be attributed to its apoptotic potential. Apoptotic property of the compounds was confirmed by the Ethidium bromide and Acridine orange double staining methods. 3β (Valeryloxy) olean-5,12-dien-1 β,11 α, 28β -triol revealed better apoptotic activity. Antitumor activity was evaluated by Daltons Lymphoma Ascites induced solid tumour model. Petrol ether extract of Justicia simplex at a dose of 200 mg/kg was capable of producing 71.74% of tumour inhibition. The newly isolated ester derivative of hederagenin and stigmasterol exhibited better cytotoxicity than the earlier reported compounds